The Formulation of an Islamic Education System - Ali Mubin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is motivated by several reasons, including: Firstly, at this time, there are philosophical foundation errors applied by educational institutions, namely that education in Indonesia is generally influenced by a Western paradigm that tends to be secular. Secondly, it is time for the Muslim community to apply educational principles based on Islamic teachings derived from the Quran and the Sunnah. As for the writing method, this study uses a normative philosophical descriptive analytical method that is adjusted to literary sources. The research results indicate that Islamic education is based on the concept of tawhid, which is an effort to effectively apply the values of Islam that can bring about a transformation of values and knowledge in its entirety to individuals, society, and the world in general, in accordance with transcendent values.